2017
DOI: 10.5194/tc-2017-56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving gridded snow water equivalent products in British Columbia, Canada: multi-source data fusion by neural network models

Abstract: Abstract. Estimates of surface snow water equivalent (SWE) in alpine regions with seasonal melts are particularly difficult in areas of high vegetation density, topographic relief and snow accumulations. These three confounding factors dominate much of the province of British Columbia (BC), Canada. An artificial neural network (ANN) was created using as predictors six gridded SWE products previously evaluated for BC: ERA-Interim/Land, GLDAS-2, MERRA, MERRA-Land, GlobSnow and ERAInterim. Relevant spatiotemporal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The results presented in Figure 10 suggest that fractal analysis could be used to create initial conditions for snow model simulations with a statistical approach (e.g., a hierarchical Bayesian model) based on (i) a model to predict basin‐wide snow depth statistics from climate forecasts and (ii) a model to predict fractal parameters using snow depth statistics. Given the nonlinear relationships found here, one could explore generalized linear models (McCullagh & Nelder, 1989), local regression methods (Loader, 1999), or machine learning techniques (e.g., Broxton et al, 2019; Snauffer et al, 2018). Ultimately, predicted fractal parameters could be used to generate an ensemble of random snow cover fields (e.g., Shook & Gray, 1997) to represent uncertainty in initial hydrologic conditions for snowmelt simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented in Figure 10 suggest that fractal analysis could be used to create initial conditions for snow model simulations with a statistical approach (e.g., a hierarchical Bayesian model) based on (i) a model to predict basin‐wide snow depth statistics from climate forecasts and (ii) a model to predict fractal parameters using snow depth statistics. Given the nonlinear relationships found here, one could explore generalized linear models (McCullagh & Nelder, 1989), local regression methods (Loader, 1999), or machine learning techniques (e.g., Broxton et al, 2019; Snauffer et al, 2018). Ultimately, predicted fractal parameters could be used to generate an ensemble of random snow cover fields (e.g., Shook & Gray, 1997) to represent uncertainty in initial hydrologic conditions for snowmelt simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Improving simulated and observation‐based gridded estimates of SWE is a major field of research (see, e.g., Snauffer et al, ; Painter et al, ), and, compared to the VIC model, more complex snow models exist. Feng et al () compared several snow models by validating them against observations and showed that VIC performs better than the complex Community Land Model, version 3 (Dai et al, ), and agrees well with the more complicated Snow Thermal Model (Jordan, ).…”
Section: Methodsmentioning
confidence: 99%
“…These statistical models, which include a variety of approaches including regression models (such as multiple linear regression—MLR), binary regression trees, and lookup tables, have been applied using observations that span both larger (e.g., continental) scales (Bormann et al, ; Sturm et al, , ) and smaller (e.g., watershed) scales (Jonas et al, ; Wetlaufer et al, ). Other machine learning approaches such as Random Forests and Artificial Neural Networks have also become popular for estimating snow quantities (particularly SWE and snow cover) using a variety of input data including data from satellite sensors (e.g., Bair et al, ; Dobreva & Klein, ; Tedesco et al, ), land surface models (e.g., Snauffer et al, ), and ground observations (e.g., Tabari et al, ; Buckingham et al, ; Gharaei‐Manesh et al, ). These approaches have been shown to be highly adaptable to capture nonlinear relationships involved in snow measurement (Czyzowska‐Wisniewski et al, ), allowing them to outperform linear approaches such as MLR.…”
Section: Introductionmentioning
confidence: 99%